Archaeological and vernacular heritage coexistence in rural areas: Didyma, Turkey - Polat, E. Omay; Aslan, E. Harman; Cetin, B. Can (CRC PRESS-TAYLOR & FRANCIS GROUP, 2014)
As in the case of the ancient ruins of Didyma, Yoran Village, is an archaeological heritage and vernacular architecture. They are located together, side by side on the top of the ancient ruins, like other multi-layered Anatolian settlements. Yoran Village dates back to 8000 B.C., and it is a rural settlement, which has the Temple of Apollo in the heart, surrounded by vernacular architecture. One or two storied courtyard-type houses and organic streets define a modest tissue, and the use of spolia on vernacular architecture supports the authenticity of the place. The village is registered as an 'archaeological conservation site' bounded by newly built up areas and agricultural lands. The aim of the study is to evaluate the data from field survey of Yoran Village, to reveal tangible and intangible values, particular to vernacular and archaeological heritage, and to discuss the potentials that will support the preservation of authentic character, in terms of integrated conservation, cultural tourism, and sustainability.
Keywords: Architecture; Engineering; Environmental Sciences & Ecology